Estudio de caso: Análisis fractal de Higuchi y Katz para señales de actígrafo de bajo costo - Martínez-Peón, D.; Islas-Valencia, L. D.; Ortíz-Jiménez, X. A.; Pérez-Encina, F. J.; Benavides-Bravo, F. G.; Góngora-Rivera, J. F. (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
The present work demonstrates a low cost actigraph to monitor motor activity while a person performs the task of going to bed. To corroborate its performance, two types of experiments were performed, in the first one the device was placed on a subject to study the first 8 hours of sleep, in the second one it was placed on a table during the same hours. Two fractal-based algorithms, Higuchi and Katz, were implemented to process the signals obtained. The signals were divided into two blocks when the device was placed on the subject, block 1 when there was a lot of motor activity once the subject was lying down, and block 2 when no motor activity was detected. ANOVA tests were run, and no significant differences were found between blocks 1 and 2, however, significant differences were found, for both algorithms, when the subject was using the device and when the device was left on the table. The implication of this result is that a device is available at low cost that can be used to verify whether the subject puts on the device to analyze motor activity or decides to take it off, for example, when they are asked to participate in an experiment that requires sleep for several hours.